Answer:
I made is clear for you, now you may match each one
Step-by-step explanation:
f(1)= 11, f(n)= 3*f(n-1)
- 11*3= 33, 33*3= 99, 99*3= 297, ...
⊕ middle
f(1)= -18, f(n)= f(n-1)+21
- -18+21= 3, 3+21= 24, 24+21= 45, ...
f(1)= -18, f(n)= f(n-1) + 22
- -18+22= 4, 4+22= 26, 26+22= 48, ...
f(1)= -18, f(n)= 2*f(n-1)
- -18*2= -36, -36*2= -72, -72*2= -144, ...
⊕ bottom
f(1)= -18, f(n)= 6*f(n-1)
- -18*6= -108, -108*6= -648, -648*6= -3888, ...
- - 18, - 108, - 648, -3888, ...
⊕ top
f(1)= 11, f(n)= f(n-1) + 22
- 11+22= 33, 33+22= 55, 55+22= 77, ...